'A Sledgehammer to Crack a Nut'? Naval Gunfire Support During the Malayan Emergency. (4th March 2017) - Paget, Steven
Abstract: The utility of naval gunfire support (NGS) during the Malayan Emergency has been the subject of significant scrutiny. While the limitations of NGS were demonstrated in Malaya, it also has proven to be extremely useful under certain circumstances. The circumstances in which NGS has proven effective during earlier and later insurgencies have generally reflected those of the Malayan Emergency. Recent operations in Afghanistan and Iraq have been less conducive to the application of maritime power, but they did not denote the end of the naval role or the potential usefulness of NGS in counterinsurgency operations. NGS is an unheralded capability, but, aside from the historical significance, it remains relevant in the contemporary era under the right conditions.